Managerial Supervision of Madrasah Principals in Optimising Administrative Digitalisation - Yusyron Abdul Arief; Muhammad Al Fatih (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The transition to digitalised school administration is frequently obstructed by internal resistance, infrastructure limitations, and inter-generational gaps in digital literacy factors whose management requires systematic supervisory intervention rather than technology procurement alone. This study analyses the strategies, challenges, and contributions of a madrasah principal’s managerial supervision in optimising administrative digitalisation, examining how each stage of a four-stage supervisory cycle operates in a real institutional context. Employing a qualitative case study design at MAN 3 Jombang, Jombang Regency (a state Islamic senior secondary school recognised as an IT Innovation Pioneer), data were collected through in-depth semi-structured interviews with six key informants (including the madrasah principal, the vice-principals for Curriculum and Facilities, the Head of Administrative Staff, and two administrative staff members), passive participant observation, and institutional document analysis. Data were triangulated across sources and methods. Findings reveal that managerial supervision operates through four integrated, circular stages. Planning involves cross-sectoral team coordination and context-sensitive modification of Ministry of Religious Affairs supervisory instruments. Implementation deploys scheduled monitoring and unannounced inspections to enforce digital documentation standards across both teaching and administrative staff. Evaluation systematically maps obstacles including digital literacy gaps among senior personnel, hardware budget constraints (IT Boards), and network reliability issues. Follow-up converts evaluation findings into structured training workshops and expert mentoring by application development teams. This supervisory cycle is associated with progressive improvements in the school’s service efficiency, with informants reporting substantial reductions in paper-based workflows and faster administrative turnaround times. Theoretically, this study extends the scope of educational supervision theory from its traditional instructional focus toward managerial governance and institutional digital transformation.